Antihypertensive therapy and hypertrichosis: a probable association. - Siva Chaitanya, Senapathi; Karthi, Kishore (European Journal of Pediatric Dermatology, 2026)
Hypertrichosis is characterized by excessive growth of terminal hair in areas of the skin where hair is normally fine, scarcely visible, or absent. The most common causes of acquired hypertrichosis include syndromic conditions, endocrine disorders, and drug exposure. Medications most frequently associated with hypertrichosis include phenytoin, minoxidil, diazoxide, cyclosporine, corticosteroids, psoralens, and acetazolamide. We report a case of acquired hypertrichosis in a 3.5-year-old child, attributed to the prolonged use of antihypertensive therapy.